Pengaruh Kualitas Layanan dan Harga Terhadap Kepuasan Penumpang Bus Trans Padang - Mega Anggraini; Rose Rahmidani (Universitas Negeri Padang, 2019)
This study aims to reveal the influence of service quality and price on the satisfaction of Trans Padang bus passengers. This research is quantitative descriptive. The population in this study were all people in the city of Padang who had used Trans Padang services, Pasar Raya - Lubuk Buaya route. The data used are primary data and secondary data. The data collection technique was using questionnaires and documentation. The sample technique used in this study was purposive sampling with a total sample of 100 respondents. The analytical method used is multiple regression analysis using the SPSS version 21 program. For hypothesis testing the study was conducted using data analysis through validity and reliability tests, normality test, multicollinearity, heteroscedicactivity, F test and statistical t test at α = 0.05. The results of this study indicate that 1) Service quality has a significant positive effect on the satisfaction of Trans Padang bus passengers 2) Price has a significant effect on the satisfaction of Trans Padang bus passengers. Keyword: service quality, price, and passenger satisfaction